Prognostic value of the infarct- and non-infarct like patterns and cardiovascular magnetic resonance parameters on long-term outcome of patients after acute myocarditis. (1st June 2016) - Chopra, Houzefa; Arangalage, Dimitri; Bouleti, Claire; Zarka, Samuel; Fayard, Florence; Chillon, Sylvie; Laissy, Jean-Pierre; Henry-Feugeas, Marie-Cécile; Steg, Philippe-Gabriel; Vahanian, Alec; Ou, Phalla
Abstract: Background: Prognostic value of the infarct- and non-infarct like patterns and cardiac magnetic resonance (CMR) parameters on long-term outcome of patients after acute myocarditis is not well known. Methods: Between 2006 and 2015, 112 consecutive patients with CMR-based diagnosis of acute myocarditis were identified in our institution. Of them, 88 were available for clinical follow-up and represented our studied population. Patients were divided into infarct-like group (n = 48) (association of acute chest pain, elevated Troponin levels and ST-elevation) and non-infarct-like group (n = 40) with any other presentation. The composite primary endpoint of major cardiovascular events (MACE) included: all-cause mortality, cardiac mortality, recurrence of myocarditis, heart failure, and sustained ventricular tachycardia. Results: During follow-up, 21 patients (24%) experienced MACE and infarct-like patients were significantly more at risk for MACE than non-infarct-like patients (HR 2.4, 95% CI [1.01–5.80] p = 0.04). Infarct-like patients exhibited in particular a higher risk of sustained ventricular tachycardia and recurrence of myocarditis (p = 0.03). They had lower CMR-derived left (p = 0.03) and right (p = 0.001) ventricular ejection fractions, and exhibited larger areas of late gadolinium enhancement (LGE) (p = 0.001). In multivariate analysis, both initial NYHA functional class > II and LGE mass were independent predictors for long-term MACE occurrence (HR 5.8 and 1.07 per gram respectively, p = 0.007). Moreover, a threshold of LGE mass > 17 g provided a high discrimination for MACE occurrence (AUC of 0.81). Conclusions: The infarct-like pattern of acute myocarditis is associated with MACE occurrence. Initial NYHA functional class > II and LGE are independent predictive factors of MACE during long-term follow-up after acute myocarditis.